Rancang Bangun Aplikasi Manajemen Kos Untuk Usaha Rumah Mulya Berbasis Mobile - Muhammad Hamrozi Yusira; Subhan Hartanto; Anton Topadang (JURNAL VOKASI TEKNIK, 2026)
Boarding house is a business entity that provides room rental services for individuals or more. Data management often poses many challenges, so it is necessary to have a tool that increases the ease of management. This research aims to develop a mobile-based boarding house management application that increases efficiency in boarding house management. This research uses the Waterfall Model, and uses the Java language and Android Studio as a development tool. The final result of this research is the creation of a mobile-based management application that features room and facility management, occupant registration management, and boarding house finances. Development suggestions include the integration of digital payments, storage of recap data, and the addition of dashboards.